Selection and coordination: The articulatory basis for the emergence of phonological structure. (March 2016) - Tilsen, Sam
Abstract: Phonological theories commonly analyze speech utterances as composed of hierarchically organized units, such as features/gestures, segments, moras, and syllables, but it is not well understood why this hierarchical organization is observed. Moreover, current phonological theories and speech production models fail to explain cross-linguistic and developmental variation in the organization of units. This paper presents the selection-coordination theory of speech production, which attempts to unify our understanding of developmental and cross-linguistic variation in phonological structure. The theory holds that hierarchical organization emerges from a recurring trend in speech development whereby children acquire coordinative regimes of control over articulatory gestures that were previously competitively selected. In this framework, segments, moras, and syllables are understood as differently-sized instantiations of the same type of motor planning unit, and cross-linguistic and developmental phonological patterns are derived from distinguishing competitive and coordinative regimes of articulatory control. Evidence for the theory is drawn from research in motor control, speech development, and phonological and phonetic patterns in speech. Highlights: The selection-coordination theory of speech production is presented. Competitive and coordinative control are related through feedback internalization. Hierarchical phonological structure emerges from control transitions. The theory explains cross-linguistic variation in phonological patterns.